EFEKTIVITAS CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM MENINGKATKAN INKLUSIVITAS EKONOMI DAN MENGURANGI KESENJANGAN SOSIAL - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study examines the effectiveness of Corporate Social Responsibility (CSR) in improving economic inclusiveness and reducing social inequality, using a literature review method. The results indicate that well-designed and implemented CSR programmes can contribute to community economic empowerment and the reduction of social inequality. Key factors influencing the success of CSR programmes include programme sustainability, active community involvement, alignment with local needs, and multi-stakeholder collaboration. However, this study also identifies several challenges and limitations in the use of CSR as a tool to address complex socio-economic issues. This study concludes that CSR can be an effective instrument in promoting economic inclusiveness and reducing social inequality, but it must be integrated with broader efforts involving government policies and civil society initiatives to achieve optimal and sustainable impact.